Implementation of Islamic Values to Strengthen Medical Student’s Professionalism at Universitas Muslim Indonesia - Khalid, Nur Fadhillah; Kamaluddin, Irna Diyana Kartika; Royani, Ida; Irwan, Andi Alamanda (Jurnal Keilmuan dan Keislaman, 2025)
Integrating Islamic values into medical education strengthens professionalism by combining clinical competence with moral and spiritual integrity. In the medical context, these values enhance empathy, compassion, and ethical conduct toward patients, families, and colleagues. To evaluate the implementation of Islamic values—tahsinul qiraah of QS. Al-Fatihah, memorization of selected Qur’anic verses and prayers, and demonstration of Islamic etiquette—in strengthening professionalism among medical students at the Faculty of Medicine, Universitas Muslim Indonesia. A descriptive, cross-sectional study was conducted with 24 clinical clerkship students completing rotations in July 2023, selected through purposive sampling. Assessment tools included standardized evaluation forms for tahsin, memorization, and patient-reported etiquette. Performance was categorized as mumtaz (80–100), ahsan (70–79), kaafii (60–69), and sayyi’ (<59). In tahsinul qiraah, 17 students (70.8%) achieved mumtaz and 7 (29.2%) ahsan. In memorization, 18 students (75%) attained mumtaz and 6 (25%) ahsan. For Islamic etiquette, 14 students (58.3%) “often” demonstrated appropriate manners, while 10 (41.7%) did so “sometimes”; none reported “never”. The strong performance in recitation and memorization reflects nearly two years of targeted training during clinical clerkship. However, etiquette implementation remains suboptimal due to limited habituation, time constraints during visits, an emphasis on medical over spiritual care, and the absence of etiquette as a summative assessment criterion. Recitation and memorization outcomes are well achieved, but Islamic etiquette in clinical practice requires reinforcement. Structured training and direct supervision by Islamic Medical Discipline (IDIK) faculty during patient encounters are recommended to embed spiritual care in medical services.